2022
DOI: 10.1108/bij-11-2021-0682
|View full text |Cite
|
Sign up to set email alerts
|

Exploring “what,” “why” and “how” of resilience in MSME sector: a m-TISM approach

Abstract: PurposeThis will not be an overstatement to state that the micro, small and medium enterprise (MSME) industry is crucial and the vital driver of the world economy. It covers different fields and dimensions such as defense products, electrical components and low-cost products. The sector plays a vital role in rendering work with low capital expenditure and is one of the emerging pillars of the Indian economy. Given the significance of this sector in contributing towards India's gross domestic product (GDP), it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 56 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…Future researchers are also encouraged to use m-TISM as a simpler and more convenient way of constructing structural explanatory models to validate their results and findings if there are fewer variables, the field of study is well established and the relevant literature is extensive. [78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93]…”
Section: Limitations and Future Workmentioning
confidence: 99%
“…Future researchers are also encouraged to use m-TISM as a simpler and more convenient way of constructing structural explanatory models to validate their results and findings if there are fewer variables, the field of study is well established and the relevant literature is extensive. [78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93]…”
Section: Limitations and Future Workmentioning
confidence: 99%
“…The second section explains the critical success factors and barriers to achieving resilience for MSMSE organisations during COVID-19. Sindhwani et al . (2023) studied the MSME industry and pointed out the directly linked enablers to improve the sector's resiliency and sustainability.…”
Section: The Special Issuementioning
confidence: 99%
“…The second section explains the critical success factors and barriers to achieving resilience for MSMSE organisations during COVID-19. Sindhwani et al (2023) studied the MSME industry and pointed out the directly linked enablers to improve the sector's resiliency and sustainability. The result of m-TISM in the current research work revealed the essential commitment of a hierarchical design dealing with the MSME considering the viewpoint of future development.…”
Section: Section Title Authorsmentioning
confidence: 99%
“…[14] Pay attention to the factors that influence the adoption of innovation in SMEs. The role of MSMEs in sustainable development needs to be explored more deeply [15]. MSMEs' marketing strategies through digital platforms can improve MSME performance [16] [17].…”
Section: Msmesmentioning
confidence: 99%